Archivists and Changing Social and Information Spaces: A Continuum Approach to Recordkeeping and Archiving in Online Cultures - Upward, Frank; McKemmish, Sue; Reed, Barbara (Archivaria, 2011)
This article looks for creative ways of addressing archiving and recordkeeping processes within the continuum of recorded information being formed in our online cultures. It is concerned with looking beyond the complexities of the social spaces and communal actions that form archives, seeking patterns that can help us reorder the relationship between communities and the way they record and store information about their transactions. The infinitely expanding, and (given the multiplicity of points of observation of that expansion) the indefinitely divisible continuum of recorded information that is the larger web sphere is a new zone of practice involving changes in the delivery of recorded information. To evolve with modern information ecologies, however, we need new forms of consciousness, new ways of viewing our functions and new tactics, structures, and strategies. This article will explore this new zone using theoretical perspectives and case studies, examining the challenge to traditional forms of archival access posed by continuum theory, WikiLeaks, and the formation of archives in Indigenous communities. RÉSUMÉ Les auteurs explorent des façons créatives d’aborder les processus d’archivage et de gestion de l’information dans le contexte du continuum de l’information qui est documenté et généré à l’intérieur de nos cultures en ligne. Ils cherchent à regarder au-delà de la complexité des espaces sociaux et des actions collectives qui créent des archives, afin de trouver les constantes qui peuvent nous permettre de réorganiser les relations entre les communautés et la façon dont elles documentent et sauvegardent l’information liée à leurs transactions. Le continuum de l’information documentée qu’est le Web est en expansion à l’infini et, compte tenu de la multiplicité des points d’observation de cette expansion, il est aussi divisible à l’infini. Il s’agit d’une nouvelle zone de pratique qui implique des changements dans la prestation de l’information. Afin de pouvoir évoluer au même rythme que l’écologie informatique, toutefois, nous avons besoin de nouvelles formes de conscience, de nouvelles façons de percevoir nos fonctions, ainsi que de nouvelles tactiques, structures et stratégies. Les auteurs examinent cette nouvelle zone en se servant de perspectives théoriques et d’études de cas qui étudient les défis posés aux formes traditionnelles de l’accès aux archives par la théorie du continuum, Wikileaks, et la création des archives des communautés autochtones.